L’exil et le retour dans les journaux filmés de Jonas Mekas et David Perlov - Jennifer Cazenave (IdeAs)
This article retraces two parallel trajectories of the diary film through an analysis of Reminiscences of a Journey to Lithuania (Jonas Mekas, 1972) and Diary (David Perlov, 1973-1983), two contemporaneous autobiographical works centered on both the experience of exile and the return to the homeland. Taking as a point of departure the theories developed by Hamid Naficy in his study of exilic cinema, we will undertake a comparative analysis of the transnational spaces constructed by Mekas and Perlov and ultimately reflect on the specificity of the diary film as a mode of representing exile.